Discovery of fluorescent 3-heteroarylcoumarin derivatives as novel inhibitors of anaplastic lymphoma kinase. Issue 1 (11th December 2018) - Mah, Shinmee; Jang, Jaebong; Song, Daesun; Shin, Yongje; Latif, Muhammad; Jung, Yongwon; Hong, Sungwoo
Abstract : Coumarin-based ALK inhibitors were identified as a new template for the development of novel fluorescent ALK inhibitors, which can be tracked using microscopy techniques. Abstract : Altered expression or hyperactivation of anaplastic lymphoma kinase (ALK), as a consequence of translocations or point mutations, is one of the main oncogenic drivers in non-small cell lung cancer. Using structure-based design and in vitro enzyme assays, we identified 3-heteroarylcoumarin as a new template for the development of novel fluorescent ALK inhibitors. Molecular simulation provided structural insights for the design of 3-heteroarylcoumarin derivatives, which were easily prepared through efficient synthetic approaches including direct C–H cross coupling. Importantly, these coumarin-based ALK inhibitors can be tracked using microscopy techniques: we illustrated the use of the most potent compound in this series, 5a, (ALK/IC50 = 0.51 μM, λ emi = 500 nm, ϕ F = 0.29) to monitor its subcellular distribution pattern by confocal fluorescence microscopy.